2019
DOI: 10.1016/j.jbo.2019.100239
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 in human osteosarcoma malignant progression. The response of osteosarcoma cell lines to the fully human CXCR4 antibody MDX1338

Abstract: Osteosarcoma (OS) is the most frequent primary malignant tumour of bone and metastases occur in 30% of cases, the 5-year survival rate is 25–30%. Although pre- and post-operative chemotherapy has improved prognosis in osteosarcoma (OS), high toxicity and natural and acquired drug-resistance are the first cause of treatment failure. The identification of new predictive and therapeutic biomarkers may increase drug sensitivity and better control localized and metastatic disease. By the evidence that CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…Previous studies have shown that CXCR4 is involved in the immune microenvironment of the tumor 26 and therefore exerts effects on cell survival, proliferation, angiogenesis, and metastasis. 19 In our study, we confirmed that in liver cancer tissues, CXCR4 expression was not only significantly associated with the infiltration levels of immunocytes but also positively correlated with biomarkers of macrophages (COX2), neutrophils (CCR7), and dendritic cells (CD1c, NRP1, and CD11c). Western blotting and IF analysis confirmed that both the mRNA expression and protein expression of CXCR4 was significantly decreased in HB cells with TUG1-knockdown.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies have shown that CXCR4 is involved in the immune microenvironment of the tumor 26 and therefore exerts effects on cell survival, proliferation, angiogenesis, and metastasis. 19 In our study, we confirmed that in liver cancer tissues, CXCR4 expression was not only significantly associated with the infiltration levels of immunocytes but also positively correlated with biomarkers of macrophages (COX2), neutrophils (CCR7), and dendritic cells (CD1c, NRP1, and CD11c). Western blotting and IF analysis confirmed that both the mRNA expression and protein expression of CXCR4 was significantly decreased in HB cells with TUG1-knockdown.…”
Section: Discussionsupporting
confidence: 80%
“…17 Targeting CXCR4 inhibited the growth and migration of malignant tumors by affecting immunocyte infiltration. 18,19 We then calculated the correlation between CXCR4 and immunocyte infiltration. We found that CXCR4 expression was significantly associated with the infiltration levels of macrophages, neutrophils, and dendritic cells in liver cancer tissues ( Figure 5A).…”
Section: Tug1 Promoted the Infiltration Of Pro-tumor Immunocytes By Rmentioning
confidence: 99%
“…High levels of CXCR4, a receptor correlated with tumor malignancy, and CCL22, a member of the chemokine family, are related to migration, invasion, and metastasis in various tumors, leading to a poor prognosis and malignant progression [58][59][60][61]. Our results show that NPs 1 and NPs 2 decrease CXCR4 and CCL22 expression in the primary microenvironment, which indicates that our nanoparticulated DDSs act as important modulators of metastatic sites.…”
Section: Discussionmentioning
confidence: 62%
“…Of note, we identified 10 hub IRGs, namely CXCR3, CXCR4, CCR5, CCL5, CXCL10, CXCL12, CXCL16, OPRL1, S1PR1, and GAL. Among them, CXCR3 28 , CXCR4 29 , CCR5 30 , CCL5 31 , CXCL16 32 , CXCL10 33 , CXCL12 34 and GAL 35 have been widely studied in OS, and are involved in the occurrence, metastasis, and angiogenesis of OS. OPRL1 encodes proteins that are endogenous opioid-related neuropeptides and nociceptin/orphanin receptors, which plays a key role in pain perception and nociception 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%